2013
DOI: 10.3746/jkfn.2013.42.11.1872
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Lactic acid Producing Bacteria from Kimchi and Their Fermentation Properties of Soymilk

Abstract: Lactic acid bacteria were selected on the basis of lactic acid producing ability from kimchi, a traditional Korean fermented food. Among the initial screening of over 150 strains selected from the sample, 27 strains were selected as lactic acid producing bacteria, and 4 strains were finally selected based on their ability to produce relatively high levels of lactic acid. The four strains were identified as Lactobacillus (L.) plantarum Gk04, Pediococcus pentosaceus Gk07, L. brevis Gk35 and L. curvatus Gk36 by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…At 96 h, the LAB counts of fermented soymilk had the range of 7.93-8.50 log CFU/g. Lee et al (2013) reported that the number of LAB in soy yogurt was highest at 24 h-fermentation: it was 8.53 log CFU/mL. Similarly, in this study, all samples showed the highest number of LAB at 24 h-fermentation.…”
Section: Microbiological Analysissupporting
confidence: 77%
See 3 more Smart Citations
“…At 96 h, the LAB counts of fermented soymilk had the range of 7.93-8.50 log CFU/g. Lee et al (2013) reported that the number of LAB in soy yogurt was highest at 24 h-fermentation: it was 8.53 log CFU/mL. Similarly, in this study, all samples showed the highest number of LAB at 24 h-fermentation.…”
Section: Microbiological Analysissupporting
confidence: 77%
“…Soymilk was boiled for 3 min and sweetener was added to it, as indicated in Table 1, and then cooled until it became 40°C. Mixed LAB starters were inoculated to 1% soymilk at the level of 10 9 CFU/mL (Lee et al, 2013) and fermented at 30°C for 96 h and used to analyze the fermentation characteristics every 24 h. The control soy yogurt was prepared by fermenting a soy milk containing only sucrose with commercial LAB (KCTC 13302 and KCTC 33131).…”
Section: Preparation Of Soy Yogurtmentioning
confidence: 99%
See 2 more Smart Citations
“…The final fermented product of A. melanocarpa was lyophilized with a vacuum freeze dryer (Operon Advantech Co., Ltd., Gyeonggi, Korea) and stored at −20 °C until use. The fermented mixture was analyzed for GABA production using thin-layer chromatography (TLC) [ 19 ] and compared with a nonfermented control sample. Before and during the fermentation, samples were collected for the measurement of different parameters, such as the pH, reducing sugar content, polyphenol content, flavonoid content, anthocyanin content, and viable cell count.…”
Section: Methodsmentioning
confidence: 99%